Die invloed van verskillende grondvogregimes op Leucospermum cordifolium (Salisb. ex Knight) Fourc. x L. lineare R. Br. cv. `Red Sunset' - Botha, A. T.(Amanda Theophila) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc.) -- Universiteit van Stellenbosch, 1980.